Toward Functional Starch Foods with Longer Shelf Life: Effects of Inulin and Konjac Glucomannan on Freeze‐Thaw Stability, Retrogradation, and Pasting Characteristics of Selected Starches. (30th November 2018) - Wang, Xiaoxuan; Reddy, Chagam Koteswara; Xu, Baojun
Abstract : In this study, the effects of the addition of inulin and konjac glucomannan (KGM) on the freeze‐thaw stability, retrogradation, and pasting viscosity of starches isolated from different botanical sources are investigated. The isolated starches complexed with inulin and KGM show significant differences ( p < 0.05) in the freeze‐thaw stability, degree of retrogradation, and pasting properties. For example, the addition of inulin (5–50%) and KGM (0.2–1.0%) to the starches, enhance the inhibition of retrogradation of all starches as well as reduce their syneresis rates. Inulin shows higher effects than KGM on the functional characteristics of isolated starches. Both inulin and KGM noticeably effect the viscosity of starches. The addition of inulin at 0–50% greatly reduces the peak, trough, breakdown, final, and setback viscosities of the starches; however, the addition of KGM at 0–10% increase these viscosities, whereas that at 10–50% decrease the viscosities. In addition, the pasting temperature increases gradually with the addition of inulin from 0 to 50%; however, the pasting temperature first increases with the addition of KGM from 0 to 20% and then decreases with further increase in KGM up to 50%. Thus, this study provides useful information for the development of functional starch foods with longer shelf life by the addition of dietary fibers, such as inulin and KGM. Abstract : In this study the effects of the addition of inulin and konjac glucomannan (KGM) on the freeze‐thaw stability, retrogradation, and pasting viscosity of starches isolated from different botanical sources are investigated. This study provides useful information for the development of functional starch foods with longer shelf life by the addition of dietary fibers, such as inulin and KGM.